Sensitivity analysis of slopes affected by possible earthquake loading and heavy rainfall: case study - Kim Huat, Bujang; Moayedi, Hossein; Asadi, Afshin; Kazemian, Sina; Keykha, Hamed A. (Academic Journals, 2011)
The effect of seismic loading on slope failure is studied both experimentally and analytically to establish the spatial and temporal process of failure initiation and propagation during possible earthquake loading or heavy rainfall. For such purpose different limit equilibrium modeling were carried out and factor of safeties against sliding caused by both excess earthquake loading and heavy rainfall were found. As for this study, two parameters normally taken into account which were soil properties changing as well as exerted seismic loading. Moreover to show the reality and importance of the main objective of this research, two of the constructed slopes in Malaysia were selected and modeled. The factor of safety against landslides in normal condition (without any extra seismic loading consideration) at Johor was 1.293, 1.425 and 1.301 using ordinary, bishop and Janbu methods, respectively. Also, factor of safety against slope failure at Besut was 1.508, 1.637 and 1.519 according to ordinary, bishop and Janbu methods, respectively. As a result, mentioned slopes will collapse applying even low seismic loading of 0.2 g. Internal friction angle reduction more than 25% also caused significant decrease in the slope’s factor of safety.